Exchange rate and political risks, again - Gregory Clare; Ira N. Gang (Rutgers University, Department of Economics, 2009)
We examine the effects of exchange rate and political risks on foreign direct investment (FDI) for multinationals. Our strategy is to examine FDI by U.S. firms at two levels: in all industries and on the subset of only firms in manufacturing industries. When investing in developed economies the firms appear to take past and present variation in exchange rates into consideration. When investing in less developed nations the past and present variation does not appear to weigh as heavily as the present and future variation. Decreasing political risk increases FDI.
Keywords: F21; F31; 330; exchange rates; foreign direct investment; uncertainty; Direktinvestition; Amerikanisch; Wechselkursrisiko; Politische Stabilität